التسول وسبل علاجه في ضوء السنة النبوية- دراسة موضوعية - - سعداني, محي الدين (University of Eloued جامعة الوادي, 2017)
عنيت الدراسة ببحث ظاهرة التسول في المجتمع الاسلامي من خلال بيان مفهوم التسول وذكر أسبابه وصوره ثم التطرق للمنهج النبوي في علاج هذه المشكلة من خلال: أولا :نهي النبي صلى الله عليه وسلم عن مد اليد بالسؤال حفظا لكرامة المسلم ودعوته الى العمل و الانتاج. ثانيا :بيان الحالات التي تباح فيها المسألة للمسلم ،ودور المجتمع في اغاثة أصحاب الحاجات. ثالثا: بيان دور الزكاة و الصدقات في الحد من ظاهرة التسول . رابعا :ذكر نماذج تطبيقية وصور عملية للتكافل المجتمعي في زمن النبي صلى الله عليه وسلم . ثم ختمت الدراسة بذكر أهم النتائج التي توصل اليها البحث , وأهم التوصيات المقترحة للطلبة و الباحثين لتشخيص هذه الظاهرة وعلاجها في المجتمع المسلم . وكذلك مدى امكانية معالجة هذه الظاهرة التسول في المجتمع من خلال التتبع الصحيح لمجرى عمل النبي صلى الله عليه وسلم والصحابة الكرام الذين اعتمدوا على المنهج المستقيم و الطريق الراقي و العمل المجد في علاج ظاهرة التسول في المجتمع الاسلامي في عصره صلى الله عليه وسلم ومدى تطبيق هذا المنهج في حلهم لمثل هذه المواقف التي كانت سارية في عصرهم ومجرى حياتهم اليومية فقد ساهموا جميعا في معالجة ظاهرة التسول و الحد من انتشارها ووضع جميع الطرق الواقية لها لضمان مجتمع اسلامي سليم من الشوائب و المصائب التي لربما تحصل له اذا اعملوا معالجة ولو ابسط الظواهر في مجتمعهم . The study aimed at investigating the phenomenon of begging in the Islamic society through a statement of the concept of begging and its reasons and its image and then address the prophetic approach in the treatment of this problem through: Firstly: The Prophet (peace and blessings of Allaah be upon him) forbade extending the hand to the question in order to preserve the dignity of the Muslim and his call to work and production. Second: A statement of the cases in which the issue is permissible for the Muslim, and the role of society in providing relief to people with needs. Thirdly: the role of Zakat and charity in reducing the phenomenon of begging. Fourth: the mention of practical models and practical images of community solidarity during the time of the Prophet peace be upon him. The study concluded by mentioning the main findings of the study, and the most important recommendations suggested for students and researchers to diagnose and treat this phenomenon in the Muslim community. As well as the extent of the possibility of addressing this phenomenon begging in the community through the correct track of the work of the Prophet peace be upon him and the honorable companions who relied on the straight approach and the high way and work glory in the treatment of begging in the Islamic community in his time and the extent of application of this approach In their solution to such attitudes that were valid in their era and the course of their daily lives have all contributed to address the phenomenon of begging and limit the spread and the development of all ways to protect them to ensure a healthy Islamic society of the impurities and calamities that may get him if they work to address even the simplest phenomena in their community
مذكرة ماستر تخصص علوم الحديث
Keywords: التسول –المسألة –العمل-الزكاة-التكافل الاجتماعي-; Begging - the issue - work - Zakat - social solidarity